Detection Malta Fever by Interferon-gamma and Steroid Hormone S Level (Indian Journal of Forensic Medicine & Toxicology, 2020)
Malta fever is one of the most common bacterial zoonosis, its causes abortion of pregnant women. Abortion is the chief obvious manifestation of Brucella infection. Brucella like better cattle placenta as a result of great concentration of erythritol sugar, whereas human placenta there is no erythritol sugar only steroid hormone, for this reason designed the our project . In this study, 100 aborted women were included , where referred to maternity and children hospital of Babylon province \ Iraq. Diagnosis of Brucella infection in these abortions was concentrated on serological and bacteriological technique. Serological studies included the use of RB and ELISA tests. Aggressive differences between RB and ELISA results have been shown. Brucella isolated and identified from aborted placenta and blood samples were 7 (7%) isolates from aborted women. Hormonal assessment by Immunohistochemical technique in Brucella infected women, showed significant decrease in progesterone expression in comparison with that aborted due to other causes, in other hand Brucella infected women showed high expression in estrogen hormones . ELISA technique was the valuable serological test to confirm the diagnosis of brucellosis as compared with RB test.